Revitalizing the Golden Fiber: Marketing Strategies and Economic Opportunities in Bangladesh's Jute Industry - Aurora, Sabia Khan; Haider, Sarder Ali (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This research seeks to shed light on the resurgence of the jute industry in Bangladesh, emphasizing its potential as a pivotal driver of the nation's economic development and its alignment with global sustainability objectives. The study further aims to map out the sector's marketing strategies, both in domestic and global contexts. Utilizing qualitative method, this research is based on the collection of primary data from interview with key industry stakeholders and observing the key points. Advanced analytical tools, including ATLAS.ti 2023, were employed to facilitate thematic and conceptual analyses, drawing connections between historical industry developments, current strategies, and future trajectories. The study delves into the prospect of Jute revitalisation and unearths the utilisation of key concepts of SWOT analysis and Ansoff matrix for the research purpose. Key findings include determining strength, weakness, opportunities, threats of the jute industry as well as strategies for value addition such as market development, market penetration, product development and diversification strategy and how to link all the concepts with practical implication